PENGARUH LIMBAH SAGU DAN PEMUPUKAN N, P DAN K TERHADAP PERTUMBUHAN BIBIT ALBIZIA (Paraserianthes falcataria L. Nielse) - Hariyadi, ,; Argasasmita, M.; Arifin, Z. (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1994)
This experiment was carried out at Cikarawang Research Station, IPB from February to July, 1992. The aim of this experiment was to study the effect of sago waste and N, P, K fertilizers on growth of albizia seedling. This experiment was arranged with Randomized Complete Block Design. There were two factors involved i.e. four different media based on the composition of topsoil and sago waste (0, 25, 50 and 70 %),' and three rates of N; P, K fertilizer. The medium consisted of topsoil and 25 % of sago waste tended to give better seedling growth than the others. Fertilization treatments did not affect seedling growth.